"Recurrent Papillary Necrosis and Nephrocalcinosis Induced by Nonsteroidal Anti-Inflammatory Drugs for Gouty Arthritis Associated with Congenital Chloride-Losing Diarrhea: A Major Risk for Kidney Loss". (16th October 2021) - El-Reshaid, Kamel; Al-Bader, Shaikha; Sallam, Hossameldin
Abstract : Congenital chloride-losing diarrhea (CCLD) is a rare genetic disorder due to autosomal recessive mutation in the SLC26A3 gene on chromosome 7. It is characterized with chronic watery diarrhea with high fecal chloride (Cl: >90 mmol/L), low potassium (K), and metabolic alkalosis with low urinary Cl and K. The overall long-term prognosis is favorable with optimal life-long salt and K supplementation. In this case report, we describe a man with progressive renal failure and small kidneys that showed nephrocalcinosis and papillary necrosis. His disease was diagnosed since birth and was confirmed by our tests. He was incompliant with therapy and had developed gout. The latter complication of his disease has led to excessive NSAID use over the past years. Reinstitution of diet, drug therapy, and allopurinol had stabilized his renal disease for 1 year of follow-up. In conclusion, excessive analgesic use is a risk factor for renal failure in CCLD.